2014
DOI: 10.1099/jmm.0.073080-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of culturable vaginal Lactobacillus species among women with and without bacterial vaginosis from the United States and India: a cross-sectional study

Abstract: Lactobacillus species play an integral part in the health of the vaginal microbiota. We compared vaginal Lactobacillus species in women from India and the USA with and without bacterial vaginosis (BV). Between July 2009 and November 2010, a cross-sectional study was conducted among 40 women attending a women's health clinic in Mysore, India, and a sexually transmitted diseases clinic in San Francisco, USA. Women were diagnosed with BV using Amsel's criteria and the Nugent score. Lactobacillus 16S rDNA was sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…They suggested that this may mean that the species found in the vaginal microbiome of healthy Indian women may vary widely from those found in women from other countries (Antonio et al, 1999). Findings from a pilot study carried out by our group using 16 sRNA in vaginal samples obtained from 40 healthy women of reproductive age (20 from each country) from Mysore, India, and San Francisco, USA, showed instead that the vaginal Lactobacillus species in both groups were similar, with L. jensenii and L. crispatus dominating all other species (Madhivanan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that this may mean that the species found in the vaginal microbiome of healthy Indian women may vary widely from those found in women from other countries (Antonio et al, 1999). Findings from a pilot study carried out by our group using 16 sRNA in vaginal samples obtained from 40 healthy women of reproductive age (20 from each country) from Mysore, India, and San Francisco, USA, showed instead that the vaginal Lactobacillus species in both groups were similar, with L. jensenii and L. crispatus dominating all other species (Madhivanan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study characterized the vaginal Lactobacillus species in women with and without BV. Detailed methods are described elsewhere (Madhivanan et al, 2014). In brief, women were assessed for eligibility based on a series of questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus crispatus has previously been identified among the vaginal microbiota (1, 2) and the intestine of chickens (3, 4). L. crispatus strain C25 was isolated from the cecal microbiota of 4-week-old female commercial white leghorn laying-type chicks (W-36, Hy-line North America, LLC, Mansfield, GA, USA).…”
Section: Genome Announcementmentioning
confidence: 99%
“…A3331-01). The cecal content were collected from bird number 337 and enriched on solid (1.5% agar) modified glucose-free MRS media containing 0.5% purified β (14) galacto-oligosaccharide (from Jose Barcena-Bruno) under anaerobic conditions (10% H 2 , 5% CO 2 , and 85% N 2 ) using a Coy anaerobic chamber (Coy Lab Products, Grass Lake, MI, USA). The isolate was selected based on its physiological and morphological properties (i.e., Gram-positive stains, non-sporeformer, rod-shaped, production of acid from glucose/lactose, acid coagulation of skim milk, inability to break down hydrogen peroxide, and 16S rRNA gene sequencing).…”
Section: Genome Announcementmentioning
confidence: 99%